Slave of algorithm: Exploring the idea of freedom, truth and value in digital age. - Abd Rahim, Mohammad Umair; Alias, Mohd Syahmir (Journal of Islamic, Social, Economics and Development, 2025)
Information technology of this age had immensely changed the way we interact and situate ourselves in the world. Although its life-improving effect is felt immediately, some thinkers and intellectuals beg to differ. Schwartz and Gertz, to name but a few, suggest that in contrast to feeling genuine freedom, screen-dependent individuals experienced ‘techno-hypnosis’. From a bird’s eye view, it is as if they are slave to what they were fed online. Algorithm-based system which gives rise to what is known as ‘Artificial Intelligence’ (AI) is the main feature of today’s information technology. In light of this, Heidegger argued that technology is not neutral because it is reciprocal of social activities. In the age where algorithm-driven platforms heavily shape our choice, the idea of freedom has to be revisited. Furthermore, in environment where information was curated by algorithms, ‘truth’ becomes susceptive to undervaluation, partly due to the seductive power of digital technology. Hence, this article examines the implications of over-reliance in digital technology towards our idea of freedom, truth and value. In achieving this, the study employs content analysis which mainly uses philosophical inference and readings such as propositional logic. The analysis introduces the idea of ‘enslavement’ to reflect on how overfeeding of algorithm impedes truth-seeking and freedom. Rather than offering normative solution, this article raises awareness of how algorithmic systems affect how we see things (worldview), especially our moral foundation; and suggests that a sound ethical framework is required in the digitally-mediated world.